DYNAMICS OF HEAT FLUXES BY BOWEN AND MATMNXFLX AND NOAH FLDAS PRODUCTS IN THE PANTANAL OF MATO GROSSO. - Duarte, Leilane Gomes; Romera, Kelly Souza; Sabino, Marlus; Curado, Leone Francisco Amorim; Palácios, Rafael da Silva; Nogueira, José de Souza (Ra'e Ga: o Espaço Geográfico em Análise, 2019)
This paper aimed to analyze the dynamics of the energy budget components: latent heat flux (LE), sensible heat flux (H) and soil heat flux (G), in the Mato Grosso Pantanal. The estimates of LE, H, and G were obtained by the Bowen ratio methods, using data from the micrometeorological tower located in the Baía das Pedras Park of SESC-Pantanal Ecological Resort, for the years 2011 to 2013. The normality of the variables Rn, LE, H and G, were tested by Kolmogorov-Smirnov test at 5% significance, and the seasonal differences of the fluxes were verified by the KruskalWallis test, α = 0.05. LE and H data from the remote sensing products MATMNXFLX and FLDAS_NOAH of the MERRA model was also acquired, and their comparison with the tower data was performed by the statistics of Spearman correlation (r), Mean Absolute Error (MAE), Root Mean Squared Erro (RMSE), bias, and Willmott's Concordance Index (d). It was observed that most of the available energy is used for evapotranspiration (latent heat), followed by sensible heat and soil heat flux. In the rainy season there is an increase in the partition of LE and G and reduction of H. Only the estimates of LE of MATMNXFLX and FLDAS_NOAH products correlate with the data observed in the meteorological tower. It is concluded that the energy partitions have a seasonal behavior and that the MATMNXFLX and FLDAS_NOAH products, after being calibrated, can be used to estimate LE in the Mato Grosso Pantanal.